2016
DOI: 10.3758/s13428-016-0717-1
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus needs are a moving target: 240 additional matched literal and metaphorical sentences for testing neural hypotheses about metaphor

Abstract: As the cognitive neuroscience of metaphor has evolved, so too have the theoretical questions of greatest interest. To keep pace with these developments, in the present study we generated a large set of metaphoric and literal sentence pairs ideally suited to addressing the current methodological and conceptual needs of metaphor researchers. In particular, the need has emerged to distinguish metaphors along three dimensions: the grammatical class of their base terms, the sensorimotor features of their base terms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
33
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 57 publications
5
33
1
1
Order By: Relevance
“…Processing fluency varied considerably as a function of context; figurativeness was fairly stable, in comparison. Then we analyzed four large datasets of metaphoric sentences, in which groups of naive participants subjectively rated metaphors along a variety of psychological dimensions such as familiarity, aptness, and metaphoricity (Cardillo et al, 2010(Cardillo et al, , 2016Katz et al, 1988;Roncero & de Almeida, 2015). Exploratory factor analyses on each dataset revealed that most of the variability in the rated dimensions (roughly 80%) could be explained by our two underlying dimensions: processing fluency and figurativeness.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Processing fluency varied considerably as a function of context; figurativeness was fairly stable, in comparison. Then we analyzed four large datasets of metaphoric sentences, in which groups of naive participants subjectively rated metaphors along a variety of psychological dimensions such as familiarity, aptness, and metaphoricity (Cardillo et al, 2010(Cardillo et al, , 2016Katz et al, 1988;Roncero & de Almeida, 2015). Exploratory factor analyses on each dataset revealed that most of the variability in the rated dimensions (roughly 80%) could be explained by our two underlying dimensions: processing fluency and figurativeness.…”
Section: Discussionmentioning
confidence: 99%
“…To gauge the construct validity of sentence-level ratings of metaphors, we present the results of two experiments and an analysis of four existing large-scale datasets of metaphorical sentences (from Cardillo et al, 2010Cardillo et al, , 2016Katz et al, 1988;Roncero & de Almeida, 2015). In both experiments, we manipulated the processing fluency of metaphors by changing the context in which they were presented.…”
Section: The Present Studiesmentioning
confidence: 99%
See 3 more Smart Citations